The Quality Level of 11thGrade's History Textbook in Kurdistan Region-Iraq in the Light of ontemporary Standards and Developing a Suggested Educational hapter in Accordance to these Standards ''Analytical and Evolutional Study'' - ألستاذ المساعد الدكتور ستار جبار حاجي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The paper aims to reveal the quality level of 11th grade's History Textbook in Kurdistan Region-Iraq in the Light of Contemporary Standards with Developing a Suggested Educational Chapter in Accordance to these Standards. The research samples is presented in the 11thgrade's History Textbook of the academic year (2017-2018) in its fourth edition printed in (2016) titled 'Modern History'. The researcher used an analytical descriptive tool to analyse and evaluate the research sample. In order to achieve the goals of the research, a tool has been prepared that consisted of (77) item, divided into (6) fields as in the following: introduction, objectives, content, aids and educational activities, assessment, and the artistic output of the textbook. After completing the process of analyzing the textbook, the results showed the following: introducing a list of Contemporary Standards to analyses and evaluate the textbook, the sample showed varying levels of compatibility with the standards from very good, good, medium, weak, and some were almost non-existent. In addition, in the light of these results, a number of recommendation and suggestion have been proposed by the researchers.